The Relationship Between Schema Modes, Psychological Flexibility, and Alexithymia with Subjective Well-Being Among Students in Qazvin - Naghash Souratgar, Kiana; Mahmoud Alilou, Majid; Hashemi Nosratabad , Touraj (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to investigate the relationship between schema modes, psychological flexibility, and alexithymia with subjective well-being among university students in Qazvin. Methods and Materials: This study was a fundamental, descriptive-correlational research conducted among students of Imam Khomeini International University during the 2022–2023 academic year. A total of 305 participants were selected using multistage cluster random sampling. Data were collected using the Satisfaction with Life Scale (SWLS), the Positive and Negative Affect Schedule (PANAS), the Schema Mode Questionnaire, the Psychological Flexibility Questionnaire, and the Toronto Alexithymia Scale (TAS-20). After obtaining informed consent, questionnaires were administered, and data were analyzed using descriptive statistics, Pearson correlation coefficients, and multiple regression analysis via SPSS. Findings: The results indicated that maladaptive schema modes (child modes, maladaptive parent modes, and maladaptive coping modes) were significantly negatively correlated with life satisfaction and positive affect and positively correlated with negative affect (p < .01). In contrast, adaptive schema modes showed significant positive correlations with life satisfaction and positive affect and negative correlations with negative affect (p < .01). Psychological flexibility was positively associated with life satisfaction (β = 0.19, p < .001) and positive affect (β = 0.42, p < .001), and negatively associated with negative affect (β = -0.23, p < .001). Alexithymia demonstrated significant negative relationships with life satisfaction (β = -0.35, p < .001) and positive affect (β = -0.38, p < .001), and a positive relationship with negative affect (β = 0.39, p < .001). Regression analyses further revealed that schema modes accounted for the largest proportion of variance in subjective well-being components, followed by alexithymia and psychological flexibility. Conclusion: The findings suggest that maladaptive schema modes and alexithymia are significant risk factors for reduced subjective well-being, whereas adaptive schema modes and psychological flexibility function as protective factors.